Upaya Meningkatkan Perencanaan Karir Siswa Berbasis Website melalui Layanan Bimbingan Klasikal di SMA - Romadoni, M. Wahyu; Setiawan, Antonius Ian Bayu (Universitas Sanata Dharma, 2024)
Based on the results of the assessment of student needs through the distribution of problem checklists, data were obtained that students experienced problems in the field of career and work. The subjects in this study were students of class X Phase E SMA Negeri 2 Yogyakarta in the 2024/2025 academic year. The focus of study in this research is to analyze the level of students' career planning ability through classical guidance services assisted by the website. The steps of counseling guidance action research carried out in three cycles include action planning (planning), action implementation, observation, and interpretation observation and reflection of the series of steps that have been implemented. The results of the study prove that there are values of students' career planning abilities in cycle I with the provision of material “the meaning and importance of career planning”, there are 35 students in the Medium category, and only 1 student in the High category. These results indicate that students' career planning skills are still low. Then, in cycle II using digital learning media in the form of a website with the provision of material “Tips and Tricks for Career Planning Information” on Study Programs in Higher Education through the “Website” Application Career planning with data results 30 students are in the High category and 6 students are in the Medium category. This indicates that the success indicator in cycle II using website media with the percentage value of the success indicator is high.